2006
DOI: 10.1590/s0004-27302006000400022
|View full text |Cite
|
Sign up to set email alerts
|

Low bone mass in children and adolescents

Abstract: Osteoporosis is a disease characterized by low bone mass and micro architectural alterations of bone tissue leading to enhanced bone fragility and increased fracture risk. Although research in osteoporosis has focused mainly on the role of bone loss in the elderly population, it is becoming increasingly clear that the amount of bone that is gained during growth is also an important determinant of future resistance to fractures. Thus, considerable interest is being placed on defining preventive strategies that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 56 publications
0
28
0
2
Order By: Relevance
“…In this study, age was addressed as a possible confounder. Bone remodeling regulatory mechanisms may vary according to age, once children and adolescents experience different stages in skeletal development [43]. In spite of that, no significant difference in cytokine measurements was found in the comparison between school age and adolescents in the control group and in patients with IH.…”
Section: Cytokinementioning
confidence: 88%
“…In this study, age was addressed as a possible confounder. Bone remodeling regulatory mechanisms may vary according to age, once children and adolescents experience different stages in skeletal development [43]. In spite of that, no significant difference in cytokine measurements was found in the comparison between school age and adolescents in the control group and in patients with IH.…”
Section: Cytokinementioning
confidence: 88%
“…Poor nutrition during childhood also increases risk for low bone density and osteoporosis. By age 17, boys have attained approximately 86%, and girls have attained approximately 93% of their maximal bone mass (Borges & Brandao, 2006;Clark, Bond, & Hecker, 2007;Fewtrell et al, 2009). Peak bone density is a major determinant of osteoporosis and fracture; failure to attain peak bone density increases risk of fracture by as much as 89% (Clark et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This pointed the necessity of future studies with populations that have low calcium intakes in order to evaluate calcium absorption and bone mass. One of the factors that determines thefracture resistance at adult age is the quantity of bone mass that was gained during the growth (Borges and Brandão, 2006), which demonstrates the importance of this kind of study in children and adolescents. Frazão and Naveira (2006), in a review of studies about the prevalence of osteoporosis in Brazil, observed a small number of studies and the necessity of implementing projects mainly in developed regions of the country aiming to use prevalence data in public health projects.…”
Section: Discussionmentioning
confidence: 99%